2021
DOI: 10.3390/ijms22042075
|View full text |Cite
|
Sign up to set email alerts
|

Costunolide, a Sesquiterpene Lactone, Suppresses Skin Cancer via Induction of Apoptosis and Blockage of Cell Proliferation

Abstract: Costunolide is a naturally occurring sesquiterpene lactone that demonstrates various therapeutic actions such as anti-oxidative, anti-inflammatory, and anti-cancer properties. Costunolide has recently emerged as a potential anti-cancer agent in various types of cancer, including colon, lung, and breast cancer. However, its mode of action in skin cancer remains unclear. To determine the anti-cancer potential of costunolide in skin cancer, human epidermoid carcinoma cell line A431 was treated with costunolide. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Moreover, COS has emerged as a potential tumor-specific candidate in skin cancer treatment. The anti-cancer activity of COS on human epidermoid carcinoma cells included the induction of apoptosis and suppression of cell proliferation and survival via various signaling pathways [ 288 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Moreover, COS has emerged as a potential tumor-specific candidate in skin cancer treatment. The anti-cancer activity of COS on human epidermoid carcinoma cells included the induction of apoptosis and suppression of cell proliferation and survival via various signaling pathways [ 288 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…[52][53][54] It is active against colorectal, cervical, hepatocellular, leukemia, breast, prostate, colon, gastric, melanoma, and lung cancer. [55,56]…”
Section: Sesquiterpenoids Artemisinin and Derivativesmentioning
confidence: 99%
“…Previous phytochemical investigations found that sesquiterpene lactones, lignans and volatile oil are the main constituents of D. souliei (Butturini et al, 2014; Tan, Jakupovic, Bohlmann, Jia, & Schuster, 1990). Especially, costunolide (cos) is considered as one of the main active sesquiterpene isolated from D. Souliei , which exerts varies pharmacological effects such as anti‐lung injury (Butturini et al, 2014), anti‐hepatitis B virus (Chen, Chou, Lee, Wang, & Yeh, 1995), anti‐ acute ulcerative colitis (Xie, Zhang, Zheng, & Shen, 2020), anti‐inflammatory (Park, Song, Kim, Park, & Kim, 2016), inhibiting alcohol‐induced gastric ulcer in mice (Zheng et al, 2016), and anti‐cancer effect (Fu et al, 2020; Lee, Cho, & Lim, 2021; Lin, Peng, & Su, 2015). Our previous study revealed that cos exerted protective activity against LPS/D‐GalN‐induced acute liver injury in mice via its anti‐inflammatory, anti‐oxidative and anti‐apoptotic capacities (Mao, Yi, Wang, Huang, & Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%